1983
DOI: 10.1111/j.1469-8749.1983.tb13725.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropathology of Propionic Acidemia

Abstract: SUMMARY The neuropathology in two biochemically documented cases of propionic acidemia is presented. While spongiform changes in white matter were seen in the infant who died at 12 days, no such changes were evident in an older patient who died at age 23 months. These findings are compared with other aminoacidemias. RÉSUMÉ Neuropathologie de l'acidémie propionique L'article rapporte la neuropathologie de deux cas bien explorés sur le plan biochimique d'acidémie propionique. Des modifications spongiformes de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Despite PA having been known for decades, there are few neuropathological reports due to its rarity (Table 3). The main neuropathological features of PA are spongiosis, neuronal loss, vacuolization, appearance of Alzheimer type II astrocytes, demyelination, and astrocytosis caused by hypoxic–ischemic injury, 9,11–14 which were also observed in this case. Vacuolization was only observed around neurons in the gray matter, and this finding is consistent with the previous study 11 .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Despite PA having been known for decades, there are few neuropathological reports due to its rarity (Table 3). The main neuropathological features of PA are spongiosis, neuronal loss, vacuolization, appearance of Alzheimer type II astrocytes, demyelination, and astrocytosis caused by hypoxic–ischemic injury, 9,11–14 which were also observed in this case. Vacuolization was only observed around neurons in the gray matter, and this finding is consistent with the previous study 11 .…”
Section: Discussionsupporting
confidence: 60%
“…Thus, neuropathological research on PA is of great significance for elucidating the mechanisms and treatments. Neuropathological reports of PA cases in the literature are exceedingly rare, and no characteristic neuropathological features have been identified yet 9–14 . Therefore, this report aims to provide an additional piece of pathological information for this rare disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Similarly, in other neuropathology reports of patients with propionic acidemia, white matter spongiosis was seen in 4 of 10 cases reported. 3,4,[24][25][26][27] In the case of neonates, the gray-white junction of the temporal cortex and white matter tracts in the brainstem are involved in spongiform degeneration. 3,25,28 In an earlier study of spongiform disorder, 29 a strong link was found between the severity of spongiform changes and reduction in apparent diffusion coefficient values.…”
Section: Discussionmentioning
confidence: 99%